IJCM_369A: Notification of malaria and dengue outbreaks during COVID-19 pandemic: A secondary analysis of weekly IDSP reporting - Babu Ullas Sathya; Hegde Pavithra; Bhargavi Madhavi (Wolters Kluwer Medknow Publications, 2024)
Background: Like many other diseases, vector borne diseases related health activities got affected during COVID-19 due to disruption in health services. The preventive measures, vector surveillance, diagnostics, early diagnosis, and management are likely to have been affected. Objective: To explore the vector-borne disease trends as outbreaks from January 2021 to December 2023 using weekly reports of Integrated Disease Surveillance Programme (IDSP). Methodology: We used the secondary data of the weekly reports of IDSP weekly reports from Jan 2020 Dec 2023. We included dengue and malaria as two important diseases to represent the prevailing vector borne diseases in the country. The outbreak data collected were entered in MS Excel and reported as frequency and proportions to visualize the time trends during the COVID-19 pandemic. Results: The outbreaks of malaria were found to occur mainly in the second half of the year with 63% and 80% outbreaks in the years 2020 and 2021 respectively, coinciding with the onset of monsoons. Maximum number of outbreaks was reported in the year of 2021, followed by 2022 with number of outbreaks being 20 and 19 respectively. Maximum number of dengue outbreaks were reported in the year 2021 followed by year 2022 with the numbers being 114 and 81 respectively. The year 2020 had around half the number of outbreaks as of the year 2022 (42 outbreaks). The first half of the year 2023 reported 25 outbreaks. Conclusion: Both malaria and dengue had maximum number of outbreaks in the year 2021 followed by a slight dip in the year 2022. At the onset of pandemic, the number of outbreaks were quite less compared to the subsequent years, probably due to the lockdown imposed.